Proposal of reducing permitted seismic damages on immovable cultural properties (building structures) - Stojnić Nedeljko; Kuzović Duško (Građevinski Materijali i Konstrukcije, 2016)
All interventions pertaining to remediation, strengthening and reconstruction of building structures (BS) in seismic areas, to which belong the immovable cultural property (ICP) buildings which are ranked as building structures (ICPBS), are constructed according to the (Code no. 52/85), [10]. This code permits structural damage of buildings without collapse in the event of the strongest earthquakes. However, this condition is unacceptable for ICPBS which have a status of high and outstandingly high importance according to the Law on Cultural property (LCP no. 71/94) [13]. Because of their special value and importance for cultural heritage ICPBS should not only survive the most intensive earthquakes, but their damage should be considerably reduced in comparison with ordinary BS. Therefore the paper proposes to divide ICPBS into three categories: ICPBS outstandingly high importance listed by UNESCO 2) ICPBS of outstanding cultural importance and 3) ICPBS of high cultural importance. For all categories, the factors for determination of ICPBS value are introduced, and therefore is determined the level of permissible damage they can be exposed to and potential risk of the loss of life in ICPBS which can be a basis for a new 'Code for strengthening and remediation of ICPBS in seismic areas', or can be appended to the existing Code no 52/85, [10].